2012
DOI: 10.1108/13522751211231987
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐methods approach for designing market‐driven packaging

Abstract: PurposeThe purpose of this paper is to demonstrate how a web‐based virtual ideation tool, dialogr.com, can be used to capture insights from consumers and to gain an understanding of consumer satisfaction with package design during and after product use. The authors also demonstrate how the resulting rich qualitative data can be combined with output from traditional survey research, to provide insight into the impact of satisfaction with package design on purchase intent.Design/methodology/approachA mixed‐metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
(73 reference statements)
0
12
0
1
Order By: Relevance
“…For example, labeling (graphic design), color, material, and form are the major elements of typical packaging and play an important role in attracting consumers' attention, raising their satisfaction, and enhancing the quality of consumers' responses to a product [15][16][17][18]. In addition, the published literature contains many discussions regarding the development of bottled products' package design based on consumers' psychological responses [5,6,19,20]. Furthermore, Becker et al (2011) indicated that the design of product packaging may attract the consumer when purchasing products [1].…”
Section: Importance Of Product Packaging Form Designmentioning
confidence: 99%
“…For example, labeling (graphic design), color, material, and form are the major elements of typical packaging and play an important role in attracting consumers' attention, raising their satisfaction, and enhancing the quality of consumers' responses to a product [15][16][17][18]. In addition, the published literature contains many discussions regarding the development of bottled products' package design based on consumers' psychological responses [5,6,19,20]. Furthermore, Becker et al (2011) indicated that the design of product packaging may attract the consumer when purchasing products [1].…”
Section: Importance Of Product Packaging Form Designmentioning
confidence: 99%
“…Although the professionals acknowledged that packaging and the product are not actively separated by the consumer, they suggested that packaging has implicit meanings that escape verbalization. The perceived quality of the packaging design has an impact on brand evaluation, intent to purchase and intent to recommend the product to others . The consumer purchases a product for a certain need or for a defined want.…”
Section: Narratives Of Consumer Interaction With Packagingmentioning
confidence: 99%
“…The perceived quality of the packaging design has an impact on brand evaluation, intent to purchase and intent to recommend the product to others. 33 The consumer purchases a product for a certain need or for a defined want. Another example of the context and the holistic nature of product-packaging unity concerned bread as a packaged product:…”
Section: Symbiotic Relationship Between Product and Packagingmentioning
confidence: 99%
“…It's known that users form their attitude towards a product at the basis of the packaging (Becker et al, 2011;Metcalf et al, 2012;Wang, 2013). For example, one study (Chandran, Batra, & Lawrence, 2009) showed that the product is perceived as a higher quality product if it is packed in a transparent bottle.…”
Section: Problem Statementmentioning
confidence: 99%